Comparison of Antimicrobial Resistance, Virulence Genes, Phylogroups, and Biofilm Formation of Escherichia coli Isolated From Intensive Farming and Free-Range Sheep - Zhao, Xueliang; Lv, Yunyang; Adam, Fathalrhman Eisa Addoma; Xie, Qingfang; Wang, Bin; Bai, Xindong; Wang, Xiaoyuan; Shan, Honghu; Wang, Xinglong; Liu, Haijin; Dang, Ruyi; Wang, Juan; et al. (Frontiers in Microbiology, 2021)
Pathogenic E. coli are among the most frequently isolated bacterial pathogens on large-scale sheep farms in China. Antibiotic use in wool sheep production is a risk factor for promoting the emergence of resistant E. coli. To reveal the differences of E. coli populations in sheep from different farming systems the antimicrobial resistance, virulence genes, biofilm formation, and phylogroups of 500 E. coli isolates obtained between September 2019 and December 2020 in northwest China from diarrheic infections of intensive farming and free-range sheep were analyzed. The antimicrobial susceptibility test for 12 classes of antimicrobial agents was determined using the broth microdilution susceptibility method, and PCR was used to detect the differences in virulence genes and phylogroups. Additionally, biofilm formation was determined using microtiter plate and slide agglutination methods. Among the 500 E. coli isolates, the majority of the isolates were multidrug resistant (75.4%) and carried at least one virulence gene (94.8%). We observed that 412 (82.4%), 360 (72.0%), and 266 (53.2%) are found to be resistant to sulfisoxazole, florfenicol, and tetracyclines, respectively. Resistance was also observed to mequindox (46.8%), ampicillin (43.6%), spectinomycin (38.6%), enrofloxacin (34.2%), ceftiofur (21.0%), gentamycin (20.4%), ceftazidime (17.8%), and polymyxin B (7.8%) but no resistance was found to meropenem. These results showed that strains from free-range subjects had fewer antibiotic resistance strains rather than sheep that were intensively farmed (P < 0.05). We observed fifteen virulence genes, of which etrA (n = 401, 80.2%) is the most common. In addition, EAEC (86.4%) is dominant among free-range sheep and EHEC (80.1%) is dominant among intensive farming. Among all virulence genes, the strongest correlation was found between etrA and papC gene (P < 0.001, OR = 455.68). Similarly, the strongest correlation was also found between eltA and sulfisoxazole (P < 0.001, OR = 877). Furthermore, the majority of the E. coli isolates belonged to phylogroup B1 (50.6%), followed by phylogroup C (20.6%), A (7.4%), E (7.4%), D (5.8%), B2 (1.6%), and F (1%). Interestingly, phylogroup B2 and D were all distributed in intensive farms. In addition, 33 (6.6%), 373 (74.6%), and 94 (18.8%) showed moderate, weak, and no connection biofilm formation ability, respectively. These data uncovered that wool sheep serve as a reservoir of pathogenic E. coli harboring multiple resistance phenotypes and virulence genes. The overlapping virulence-associated traits between IPEC and ExPEC indicated the zoonotic potential and safety threats of sheep food products. It is urgent to improve the proper use of antimicrobials in China as well as other countries.